A study on audit report timeliness: The Macedonian Stock Exchange - Dušica Stevčevska-Srbinoska; Igor Srbinoski (International Journal of Management and Economics, 2021)
Financial statements reflect important information about the entity's financial position, operating performance, and cash flows and must be made available in a timely fashion to all interested factions to stimulate opportune business judgments. Ergo, this paper examines the association of the audited annual report delay with eight entity and audit firm attributes. The sample includes 396 observations of 99 nonfinancial firms listed on the Macedonian Stock Exchange (MSE) for the period 2014-2017. The regression results designate a statistically significant relationship between the audit opinion, company liquidity, size, and industry with the audit opinion lag. Moreover, the publication period ranges from 43 days to 374 days suggesting that timeliness may be a significant concern for Macedonian entities regarding financial reporting policy. This is the first study to thoroughly assess the relationship between entity, auditor characteristics, and audit report timeliness on the developing Macedonian market.
Keywords: M41; M42; 650; audit opinion; annual reports; company size; financial indicators; Macedonian Stock Exchange; timeliness